ZAMBIA'S MENTAL HEALTH PATIENTS: VICTIMS OF UNSPEAKABLE INFRASTRUCTURE CHALLENGE IN ZAMBIA'S HEALTH SYSTEM - Chilufya, Kapumpe (Global Journal of Health Sciences, 2022)
Purpose: This article attempts to examine the critical role that physical health infrastructure and associated facilities play in the delivery of effective integrated primary health care services for mental patients in Zambia. The working definition for "˜physical infrastructure' in the paper relates to wider capacities in form of hospital buildings, bed spaces, medical equipment, and professional healthcare personnel, among other elements that facilitate effective operations of a health facility. Methodology: This study has used both quantitative and qualitative data from various sources to map the debate on the impact of inadequate infrastructure on mental health patients in Zambia's health system. Findings: Inadequate health infrastructure has had a negative impact on the well-being of mental health patients and other sectors of the Zambian society. The entire country has only one ill-resourced main hospital, offering mental health services and has been overwhelmed by a combination of insufficient infrastructure and effects of COVID-19 pandemic. Unique contributions to theory, practice, and policy: For the health reforms to be effective, it is recommended that the conceptual integrated health system in Zambia be anchored on universal allocation of adequate resources and operationalization of mental health policies that genuinely connect with social determinants of mental health issues within communities. The involvement of non-governmental organizations providing an interface between communities and governments should be supported by organizational and multi-institution capacity and coordination. A systems theory informed this study and has been elaboratively discussed in the second chapter of this paper